Role and clinical course of verotoxigenic Escherichia coli infections in childhood acute diarrhoea in Argentina - Rivero, Mariana Alejandra (2010)
The aim of the study was to investigate the role and clinical course of verotoxigenic Escherichia coli (VTEC) infections in children with acute diarrhoea from Argentina, the country with the highest worldwide incidence of haemolytic uraemic syndrome (HUS). To accomplish our objective, 437 samples from children up to 6 years old with acute diarrhoea were collected and processed. More than 60% of the children studied presented watery or mucous diarrhoea without blood, and in 25.2% of the cases the samples were with blood. In a first screening, a multiplex PCR was performed to detect the presence of vt1, vt2, eae, ehxA, saa virulence genes Then, the strains were isolated and analyzed in order to characterize their serotypes, virulence genes, antibiotic susceptibility profiles and verotoxin (VT) production. Forty four of the 437 samples (10.06%) were positive to VTEC virulence genes. VTEC-infected patients presented different types of diarrhoea (27.27% belonged to non-bloody type). Several serotypes and virulence genotypes were found. Isolates belonged to the serotypes O157:H7, O145:H-, O26:H11, O121:H19, O111:H2, and O118:H2. HUS developed in 16 (36.4%) patients corresponding to positive samples. All the VTEC isolates produced a cytopathic effect on Vero cells monolayer, confirming the ability for VT expression. Despite most strains were sensitive to all antimicrobials studied a positive association between clinical progression to HUS and antibiotic therapy, both for the total of patients studied, as well as for the VTEC-positive group was observed. In conclusion, the data obtained in this study increase the knowledge on the role and clinical course of VTEC infection in childhood acute diarrhoea beyond bloody diarrhea, and might be considered for the prevention, diagnosis and management of this disease. It is possible that the optimal approach for VTEC diagnosis could be through searching by multiplex PCR for the presence of vt1, vt2, eae and ehxA genes.